1. y ={ 2x }^{ 2 } +7x-3

 Quantity A Quantity B x y

2. \frac{ 1-x }{ x-1 }=\frac{ 1 }{ x }

 Quantity A Quantity B x -\frac{ 1 }{ 2 }

3. (x+3)(y-4)=0

 Quantity A Quantity B xy -12

4. If both expressions { x }^{ 2 }-3x+2 and { x }^{ 2 }-4x+3 equal 0, then what is the value of { (x-3) }^{ 2 } ?

(A) 0
(B) 1
(C) 2
(D) 3
(E) 4

5. If x + y = 7 and { x }^{ 2 }+{ y }^{ 2 } = 25, then which one of the following equals the value of { x }^{ 3 }+{ y }^{ 3 } ?

(A) 7
(B) 25
(C) 35
(D) 65
(E) 91

6. (x-2y)(x + 2y) = 5
(2x-y)(2x + y) = 35

 Quantity A Quantity B { 2x }^{ 2 }-{ y }^{ 2 } { x }^{ 2 }-{ 2y }^{ 2 }

7. a = 49, b = 59?

 Quantity A Quantity B \frac{ { a }^{ 2 }-{ b }^{ 2 } }{ a-b } \frac{ { a }^{ 2 }-{ b }^{ 2 } }{ a+b }

8. If { x }^{ 2 }-4x + 3 = 0, then what is the value of { (x-2) }^{ 2 } ?

(A) -1
(B) 0
(C) 1
(D) 3
(E) 4

9. If \sqrt { 3-2x }=1, then what is the value of (3-2x) + { (3-2x) }^{ 2 } ?

(A) 0
(B) 1
(C) 2
(D) 3
(E) 4

10.

 Quantity A Quantity B { 1111.0 }^{ 2 }-{ 999.0 }^{ 2 } { 1111.5 }^{ 2 }-{ 999.5 }^{ 2 }

11. (x-2)(x + 4)-(x-3)(x-1) = 0

(A) -5
(B) -1
(C) 0
(D) 1/2
(E) 11/6

12. If x + y = k, then 3{ x }^{ 2 } + 6xy + 3{ y }^{ 2 } =

(A) k
(B) 3k
(C) 6k
(D) { k }^{ 2 }
(E) 3{ k }^{ 2 }

13. 8{ k }^{ 2 }-18 =

(A) 8({ x }^{ 2 }-2)
(B) 2(2x + 3)(2x-3)
(C) 2(4x + 3)(4x-3)
(D) 2(2x + 9)(2x-9)
(E) 2(4x + 3)(x-3)

14.  4x + y + 3z = 34
4x + 3z = 21
What is the value of y

15.

 Quantity A Quantity B (2s + 1)(s + 5) 2{ s }^{ 2 } + 11s + 4

1 D
2 B
3 D
4 E
5 E
6 A
7 A
8 C
9. C
10 B
11 E
12 E
13 B
14 13
15 A